Nuclear modification factor of neutral pions in the forward and backward regions in p-Pb collisions - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2023)
The nuclear modification factor of neutral pions is measured in proton-lead collisions collected at a center-of-mass energy per nucleon of 8.16 TeV with the LHCb detector. The π0 production cross section is measured differentially in transverse momentum (pT) for 1.5<pT<10.0 GeV and in center-of-mass pseudorapidity (ηc.m.) regions 2.5<ηc.m.<3.5 (forward) and −4.0<ηc.m.<−3.0 (backward) defined relative to the proton beam direction. The forward measurement shows a sizable suppression of π0 production, while the backward measurement shows the first evidence of π0 enhancement in proton-lead collisions at the LHC. Together, these measurements provide precise constraints on models of nuclear structure and particle production in high-energy nuclear collisions.